Longitudinal fluctuation in mammographic percent density differentiates between interval and screen‐detected breast cancer. Issue 1 (24th September 2016) - Strand, Fredrik; Humphreys, Keith; Eriksson, Mikael; Li, Jingmei; Andersson, Therese M. L.; Törnberg, Sven; Azavedo, Edward; Shepherd, John; Hall, Per; Czene, Kamila
Abstract : Interval breast cancer (IC) has a more aggressive phenotype and higher mortality than screen‐detected cancer (SDC). In this case‐case study, we investigated whether the size of longitudinal fluctuations in mammographic percent density (PD fluctuation) was associated with the ratio of IC versus SDC among screened women with breast cancer. The primary study population consisted of 1, 414 postmenopausal breast cancer cases, and the validation population of 1, 241 cases. We calculated PD fluctuation as the quadratic mean of deviations between actual PD and the long‐term trend estimated by a mixed effects model. In a logistic regression model we examined the association between PD fluctuation and IC versus SDC including adjustments for PD at last screening, age at diagnosis, BMI and hormone replacement therapy. All statistical tests were two‐sided. There were 385 IC and 1, 029 SDC in the primary study population, with PD fluctuations of 0.44 and 0.41 respectively ( p = 0.0309). After adjustments, PD fluctuation was associated with an increased ratio of IC versus SDC, with an estimated per‐standard deviation odds ratio of 1.17 (95% CI = 1.03–1.33), compared to 1.19 (95% CI = 1.04–1.38) in the validation population. In screened women with breast cancer, high fluctuation in mammographic percent density was associated with an increased ratio of IC versus SDC. Whether this is entirely related to a reduced mammographic detectability or to a biological phenotype promoting faster tumor growth remains to be elucidated. Abstract : What's new? Interval breast cancers, tumors that spring up between screenings, tend to be more aggressive and deadly than cancers detected by a mammogram. To find out exactly how breast tissue density affects the likelihood of developing such cancers, these authors combed through mammogram data from thousands of breast cancer patients. Their analysis shows that interval cancers occur more frequently in women whose breast density fluctuates more than usual from screening to screening. It's not yet clear whether this is because of something biologically intrinsic to the tumors, or if changing breast density interferes with mammographic detection of tumors.